Cohort Profile: The Australian Longitudinal Study of Ageing (ALSA). (1st December 2014) - Luszcz, Mary A; Giles, Lynne C; Anstey, Kaarin J; Browne-Yung, Kathryn C; Walker, Ruth A; Windsor, Tim D
Abstract: In response to the expressed need for more sophisticated and multidisciplinary data concerning ageing of the Australian population, the Australian Longitudinal Study of Ageing (ALSA) was established some two decades ago in Adelaide, South Australia. At Baseline in 1992, 2087 participants living in the community or in residential care (ranging in age from 65 to 103 years) were interviewed in their place of residence (1031 or 49% women), including 565 couples. By 2013, 12 Waves had been completed; both face-to-face and telephone personal interviews were conducted. Data collected included self-reports of demographic details, health, depression, morbid conditions, hospitalization, gross mobility, physical performance, activities of daily living, lifestyle activities, social resources, exercise, education and income. Objective performance data for physical and cognitive function were also collected. The ALSA data are held at the Flinders Centre for Ageing Studies, Flinders University. Procedures for data access, information on collaborations, publications and other details can be found at [http://flinders.edu.au/sabs/fcas/ ].